PERBANDINGAN STABILITAS FISIS SEDIAAN NANOEMULSI MINYAK BIJI DELIMA DENGAN FASE MINYAK LONG-CHAIN TRIGLYCERIDE DAN MEDIUM-CHAIN TRIGLYCERIDE - Sri Hartanti Yuliani; Medaliana Hartini (Majalah Obat Tradisional, 2016)
Pomegranate seed oil has antioxidant, anti-inflammatory, and chemo preventive activities. Pomegranate seed oil is lipophilic substance suitable to be prepared in emulsion dosage forms. Long-chain triglyceride (LCT) and medium-chain triglyceride (MCT) are commonly used as oil phase in emulsion dosage forms. This research aimed to compare the use of LCT and MCT in the Nano emulsion formula of pomegranate seed oil dosage forms. Formulation of pomegranate seed oil Nano emulsion was conducted using high energy emulsification. Parameters observed were pH, Nano emulsion type, percent transmittance, viscosity, turbidity, and droplet size before and after 3 cycles of freeze-thaw. The result showed that there was no significant difference between physical properties of pomegranate oil Nano emulsion with LCT as oil phase and pomegranate oil Nano emulsion with MCT as oil phase. Moreover, physical stability of pomegranate oil Nano emulsion with LCT as oil phase was better than pomegranate oil Nano emulsion with MCT as oil phase.